Abstract Reduction Systems and Idea of Knuth-Bendix Completion Algorithm - Bancerek, Grzegorz (Formalized mathematics, 2014)
Educational content for abstract reduction systems concerning reduction, convertibility, normal forms, divergence and convergence, Church- Rosser property, term rewriting systems, and the idea of the Knuth-Bendix Completion Algorithm. The theory is based on [1].